(untitled) (Journal of the College of Basic Education, 2023)
The character of Lord Stanley, as a British statesman and politician, has been subjected to many contacts. And to summarize his achievements, his eradication of slavery in Britain, the education of Ireland, and the reformation of The British Parliament in 1832 and carried out a major democratic reform in 1832. 1867 and took All of these roles are on his shoulders. Lord Stanley started as a member of the Whigs party and became its leader and advocate of trade free. Then I move on